2012
DOI: 10.1111/j.1420-9101.2012.02591.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic recombination in the ever‐young sex chromosomes of Hylid frogs

Abstract: Sex chromosomes are expected to evolve suppressed recombination, which leads to degeneration of the Y and heteromorphism between the X and Y. Some sex chromosomes remain homomorphic, however, and the factors that prevent degeneration of the Y in these cases are not well understood. The homomorphic sex chromosomes of the European tree frogs (Hyla spp.) present an interesting paradox. Recombination in males has never been observed in crossing experiments, but molecular data are suggestive of occasional recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 31 publications
5
54
0
Order By: Relevance
“…That region could be physically large and span many loci, however, if the recombination rate per megabase is low in Y chromosomes. That seems to be the case in some taxa: in hylid frogs the Y recombines with the X at a rate that is several orders of magnitude lower than the rate between two X chromosomes (Guerrero et al 2012a), so almost all of the sex chromosomes consist of a PAR that is very tightly linked to the SDR. The size of the region showing substantial divergence between X and Y could also be large if there are multiple loci under SA selection in the PAR, since they can reinforce each other's effects and facilitate polymorphism (Patten et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…That region could be physically large and span many loci, however, if the recombination rate per megabase is low in Y chromosomes. That seems to be the case in some taxa: in hylid frogs the Y recombines with the X at a rate that is several orders of magnitude lower than the rate between two X chromosomes (Guerrero et al 2012a), so almost all of the sex chromosomes consist of a PAR that is very tightly linked to the SDR. The size of the region showing substantial divergence between X and Y could also be large if there are multiple loci under SA selection in the PAR, since they can reinforce each other's effects and facilitate polymorphism (Patten et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Despite absence of male recombination in all 3 species, conspecific X and Y homologs display strong sequence similarities and cluster phylogenetically by species, not by gametologs [Stöck et al, 2011b]. Analyzing the patterns of allelic similarity by Approximate Bayesian Computation, Guerrero et al [2012] confirmed a role for rare X-Y recombination, estimated to be approximately 10 -5 less frequent than X-X recombination. However, because rare X-Y recombination is sufficient to homogenize X and Y allele frequencies, sex-linked loci were usually not diagnostic at the population level.…”
mentioning
confidence: 81%
“…Our data also possibly suggest a reduced fitness in sexreversed individuals, originating from perturbations of gonadal development, and compatible with the action of sex-antagonistic genes on the sex chromosomes. Thus, the rarity of X-Y recombination [Guerrero et al, 2012] might stem not only from the low occurrence of XY females but also from their low fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, a recent analysis of neutral genetic variation on the sex chromosomes provides statistical support for a low rate of X-Y recombination in European tree frogs (Hyla spp.) (Guerrero et al 2012b), a group of species with cryptic sex chromosomes and stable sex determination (Stöck et al 2011). Furthermore, a theoretical study of mutation accumulation on the sex chromosomes shows that occasional sex reversal events provide sufficient opportunity for recombination to purge the Y chromosome from its deleterious mutation load (Grossen et al 2012).…”
Section: Genetic and Developmental Architecturementioning
confidence: 99%